O uso das tecnologias da informação e comunicação (TICs) como instrumento mediador no processo ensino-aprendizagem - Brito, Julio César Siqueira (Universidade Federal Rural do Semi-Árido, 2019)
The present study deals with the use of information and communication technologies (ICTs) as a mediating instrument in the teaching-learning process. The research field of this investigation was conceived in a State School of High School located in the Municipality of Lajes-RN. For the elucidation of this study, authors such as CRUZ SILVA (2012) were used as theoretical-methodological input; KENSKI (2003); VOLPATO and IGLESIAS (2014); MORAN (2000); PRADO (2001); FREIRE (2001); LÍBANEO (2006) and GIL (2008), among others. The aim is to investigate and analyze the relationship between the use of Information and Communication Technologies (ICTs) as a mediating instrument in the teaching-learning process based on pedagogical practices. This monographic construct is based on the bibliographical and field research carried out with a qualitative, interpretative / reflexive and dialogical character. In order to reach our objectives in the research, the following methodological procedures were used to construct data: semi-structured interviews, questionnaires and observations, which intermediarized our dialogues together with the research subjects, manager, teachers and students, as well as allowed to enter the field of research, make a survey of available technological resources and analyze the use of these. The analysis of the methodological course enabled us to describe the results constructed in the field of research, to understand the use of technological resources in the teachers' practice and in the school context, as well as the importance of this use, through the observation when using ICT as mediation pedagogical In the research findings we find among other issues the needs of teaching in relation to continuing education, which presents itself as a condition for the adequate use of ICT in teaching-learning, providing a more meaningful educational environment.
Monografia
Keywords: Tecnologias digitais; Ensino-aprendizagem; Práticas pedagógicas; Digital technologies; Teaching-learning; Pedagogical practices; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA